Phytoremediation of Stormwater by Floating Treatment Wetland - Nuruzzaman, Md; Anwar, Faisal; Sarukkalige, Ranjan (2022)
Floating treatment wetland (FTW) is a promising technology for nutrient and metal removal from stormwater. Plant is the key component of an FTW, facilitating pollutant removal through plant uptake and microbial actions. A careful selection of plant species is essential for an efficient FTW. This paper reviews available literature focusing on the role of plants in FTWs to identify research gaps and provide future research directions. From field-scale research, it was identified that Baumea articulata, Phragmites australis, Chrysopogon zizanoidses and Carex appressa were high-performing plants for nitrogen and phosphorus removal. It was found that the presence of microbial community largely depends upon the plant species. Microbial species and abundance are also limited by environmental factors such as pH, dissolved oxygen and nutrient concentration. Multi-species plantation is widely adopted in field-scale FTWs, but its effectiveness is not proven even though it has the potential for enhanced treatment under the right condition. Development of plant harvesting strategies for permanent removal of pollutants from the FTW system was found to depend on the season and nutrient distribution in plant tissue. This review paper provides critical insights into plant selection, role of microbes, multi-species plantation and harvesting strategies for permanent removal of pollutants from an FTW system.